2019
DOI: 10.1093/eurheartj/ehz748.0236
|View full text |Cite
|
Sign up to set email alerts
|

P1471Multimodality imaging of left ventricular function and volumes in patients with acute and chronic myocardial injury - Novel insights

Abstract: Introduction The three main techniques to evaluate myocardial function and volumes: two-dimensional echocardiography (TTE), gated single photon emission computed tomography (SPECT) and cardiac magnetic resonance imaging (cMRI), have important differences in accessibility and practicality. Purpose We aimed to evaluate: TTE, SPECT and cMRI in the measurement of left ventricular ejection fraction (LVEF), left ventricular end-dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…First, the size of our substudy was limited. Second, the protocol did not include multimodal imaging to evaluate left ventricular function; however, our recent study showed a strong concordance between LVEF derived from echocardiography, single-photon emission computed tomography, and cardiac magnetic resonance imaging [ 24 ]. Third, cardiac biomarkers although sampled were not available to the present analysis.…”
Section: Discussionmentioning
confidence: 99%
“…First, the size of our substudy was limited. Second, the protocol did not include multimodal imaging to evaluate left ventricular function; however, our recent study showed a strong concordance between LVEF derived from echocardiography, single-photon emission computed tomography, and cardiac magnetic resonance imaging [ 24 ]. Third, cardiac biomarkers although sampled were not available to the present analysis.…”
Section: Discussionmentioning
confidence: 99%